ANALYSIS OF EMERGENCY AMBULANCE RECALLS AMONG PATIENTS WITH HIGH BLOOD PRESSURE IN MOSCOW - N. F. Plavunov; N. I. Gaponova; V. A. Kadyshev; V. S. Filimonov; A. E. Akimov; A. S. Bezymyannyy; A. Y. Krasilnikov (SINAPS LLC, 2017)
Over the last years the incidence of cardiovascular diseases had increased in Russian Federation. In a period of 2010-2014 y. the number of patients diagnosed hypertension increased by 16,8% (139,5 thousand patients). High prevalence of hypertension leads to different cardiac complications that could be responsible for death. Hypertension is a major risk factor for ischemic heart disease and stroke, increases the risk in 3-4 times, and therefore one of the most important causes of morality. The major cause that required emergency hospitalization in adult population was estimated to be cardiovascular diseases (23,9%), including ischemic heart disease (10,7%), cerebrovascular diseases (6%), and diseases attributable to high blood pressure (3,3%). We studied 1 605 374 (9,6%) emergency ambulance calls to patients with high blood pressure during the period of 6 month (2015 y.) . In 16,1% cases emergency service calls were related to hypertensive crisis and 1,45% of patients needed emergency evacuation. We determined that in 7,2% cases patients with high blood pressure called for emergency service again during 24 hours period. Among this group of patients the percent of hypertensive crisis and evacuation was higher - 19,4% and 4,1% respectively. Also we identified that in 59,5% cases the diagnosis was hypertensive disease. We determined that majority of frequent ambulance callers were elderly persons.